PENERAPAN PRINSIP-PRINSIP RESTFUL API DALAM PENGEMBANGAN WEB SERVICE PADA NEO FEEDER DENGAN FRAMEWORK LARAVEL: PENERAPAN PRINSIP-PRINSIP RESTFUL API DALAM PENGEMBANGAN WEB SERVICE PADA NEO FEEDER DENGAN FRAMEWORK LARAVEL - Ula, M. Izul; Kusrini, Kusrini; Muhammad, Alva Hendi (Nusantara of Engineering (NOE), 2024)
With advances in technology, the use of fire is very helpful in the development process of the data in the Neo Feeder which is directly integrated into the Higher Education and Higher Education. The presence of a web service in the Neo Feeder makes it easier to retrieve data as needed in the development process. This research uses the Representational State Transfer (RESTFUL) Web Service method. RESTFULL web service is a technological method that applies the concept of moving between states using a browser or also called the HTTP mechanism to connect applications with other applications. In this case the RESTFULL method is used as data access to the local database (SIAKAD) which aims to facilitate development and provide updated information. Based on the results of the tests that have been carried out, it can be concluded that functionally all processes in the system using the RESTFULL Web Service method have run as expected and can reduce actual information (Syafrial, M., & Teguh, I. 2019).